Anonymous
Anonymous asked in Science & MathematicsMathematics · 1 decade ago

Can you help me find the first and second derivative?

C(u) = (k+((c)(lambda)(u))) / (1 - e^-(alpha)(u))

1 Answer

Relevance
  • cidyah
    Lv 7
    1 decade ago
    Favorite Answer

    Use the Quotient Rule.

    = [1-e^(-alpha(u)] [k+(c)(lamba)] - [k+(c)(lamda)(u)) (-e^(-alpha(u)) (-alpha)] / (1-e^(-alpha)(u)]^2

    Note:

    if f(x) = h(x)/g(x)

    f'(x) = [g(x) h'(x) - h(x) g'(x)] / [g(x)]^2

    here h(x)=(k+((c)(lambda)(u)))

    g(x)=(1 - e^-(alpha)(u))

Still have questions? Get your answers by asking now.